Implementasi P5 dalam Menumbuhkan Kreativitas Siswa Melalui Pemanfaatan Minyak Jelantah Menjadi Lilin Aromaterapi di Kelas VB SD Negeri 63 Palembang - Ahmad Sallul Azromi; Maharani Oktavia (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) in fostering student creativity through the use of used cooking oil to make aromatherapy candles in Class VB at SD Negeri 63 Palembang. The background of this study is based on the still low level of students’ creativity, both in cognitive and non-cognitive aspects, such as difficulty in expressing ideas, lack of self-confidence, and limitations in collaboration. Additionally, learning that remains largely conventional and the lack of teachers’ experience in implementing project-based learning also pose challenges. This study employed a qualitative approach, focusing on the planning, implementation, and evaluation processes of P5 activities centered on the theme of sustainable living through the utilization of household waste—specifically used cooking oil—processed into aromatherapy candles. The learning process actively engaged students from the observation stage, through material processing, to the creation of the final product, thereby providing a contextual and meaningful learning experience. The results of the study indicate that the implementation of P5 through the aromatherapy candle-making activity is capable of enhancing students’ creativity, as evidenced by their ability to generate ideas, innovate, and collaborate and solve problems; furthermore, this activity fosters an attitude of environmental stewardship and an awareness of the importance of a sustainable lifestyle. It can therefore be concluded that the implementation of P5 through real-world projects serves as an effective learning alternative for developing students’ creativity and character in a holistic manner.